(untitled) (Scientific journal of the Fergana State University, 2024)
This article discusses issues related to the origin of obsolete words in linguistics, their importance, types and dictionaries. Here, the importance of historical words is revealed more clearly through the conclusions and analyzes of scientists related to the field. In addition, a discussion of the lexicography of historical words and their use, problems, and shortcomings is provided.